Efficiency of waste as cement replacement in foamed concrete—A review - Rokiah, Othman; Putra Jaya, Ramadhansyah; Duraisamy, Youventharan; Sulaiman, Mohd Arif; Wei Chong, Beng; Ghamari, Ali (MDPI, 2023)
Foamed concrete is a lightweight construction material that has gained popularity due to its excellent thermal and acoustic insulation properties. Foamed concrete production involves using cement as a binding agent, which results in a high carbon footprint. In response to sustainable development goals (SDG), there has been a growing interest in exploring alternative materials that can replace cement to improve energy efficiency, climate change, resource efficiency, and overall improvement of foamed concrete properties. Several tons of waste generated annually from industry, agriculture, and quarries are dumped into landfills and cause environmental impacts. Nevertheless, the efficiency of this waste presents an interesting question and there is limited knowledge of its use in foamed concrete. Hence, a review study is needed to evaluate the efficiency of different waste materials that could be used to replace cement in foamed concrete production. The objective of this research is to summarize the efficiency of industrial waste (IW) as a pozzolan alternative (PA) for cement replacement in foamed concrete (FC) production. This study aims to evaluate the chemical, physical, and pozzolanic reactions of selected IW and compare them to cement and selected pozzolans to determine the effect of efficient IW on the compressive strength and durability of FC. This research evaluated the efficiency of IW in PA by characterizing their chemical, physical, and pozzolanic reactions. The selected IW was studied and compared to cement and selected pozzolans using XRF and XRD analyses. This study also performed the Frattini test to determine the strength activity index (SAI) of efficient IW. The efficiency of IW in PA was evaluated by comparing the SAI of efficient IW to the minimum 75% required by BS3892. The compressive strength and durability of FC with efficient IW were determined by evaluating the microstructure of the hardened paste of FC using capillary void analysis. The study found that efficient IW, which was classified as siliceous pozzolan type F (ASTMC618-SAF > 70%), rich in amorphous silica and a high Blaine specific area, can replace cement in FC production. The XRF and XRD results showed that the m ost crystalline components obtained in the IW are SiO2 , Al2O3, CaCO3, and Fe2O3 . The efficient IW produced more calcium silicate hydrate (CSH) and denser FC, making it stronger, with fewer voids and higher resistance to water absorption. The Frattini test showed that the SAI of efficient IW is greater than the minimum 75% required by BS3892. Incorporating efficient IW as cement replacement in FC produced higher compressive strength and improved the durability of FC. The novelty of this research is in the evaluation of efficient IW as a replacement material for cement in FC production. This study shows that efficient IW can promote the use of waste materials, reduce CO2 emissions, conserve energy and resources, and improve the properties of FC. This study’s findings can be used by construction industry players to support sustainable development goals by reducing the use of cement and promoting the use of waste materials as a replacement material for cement.